การตรวจหาเชื้อเอชไอวีดื้อต่อยา ต้านไวรัสและความสำคัญของ ฐานข้อมูลที่ใช้ในการวิเคราะห์ผล - อธิปัญญาศิลป์ นิรชา (Siriraj Medical Bulletin, 2018)
Highly active antiretroviral therapy (HAART) regimen can effectively suppress HIV replication and induce immune restoration; however, extensive use of antiretroviral agents has increased drug resistance. Genotypic assay detects nucleotide mutations in protease and reverse transcriptase genes associated with antiretroviral resistance. The interpretation of genotypic assay usually varies between laboratories depending on the systems of HIV drug resistance database, such as Stanford, Agence Nationale de Recherche sur le SIDA (ANRs), and Rega. These systems use different bioinformatics tools to construct the mathematical model for drug resistance prediction, causing the discrepancy results. Moreover, the HIV subtype B is normally used as a reference strain, which is not correlated with the circulating strain in Thailand, CRF_01AE. Incorrect interpretation when using this reference strain for CRF_01AE samples was reported in this study. Thus, the development of HIV database using CRF_01AE as a reference strain will improve the precise interpretation of HIV drug resistance detection.